State of the Debate on Agri-Food Systems Transformation - El Hage Scialabba, Nadia; Zitterbarth, Sarah; Shah, Tavseef Mairaj; Caron, Patrick; Hamm, Michael; Kimani-Murage, Elizabeth; Martínez-Cruz, Tania; Merrigan, Kathleen; Mooney, Pat; Fleckenstein, Martina; Mulet, Michael; Müller, Alexander; et al. (Think Tank for Sustainability, 2023)
The second report, State of the Debate on Agri-Food Systems Transformation, conducts a critical discourse analysis to examine alignment, as well as divergence in current understanding of agrifood systems and potential pathways for agri-food systems transformation. The analysis further reveals important blind spots that have only been marginally addressed in the transformation debate but are essential for a holistic approach.